2021
DOI: 10.1093/nar/gkab660
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism of enhanced transcription activity and fidelity for influenza A viral RNA-dependent RNA polymerase

Abstract: During RNA elongation, the influenza A viral (IAV) RNA-dependent RNA polymerase (RdRp) residues in the active site interact with the triphosphate moiety of nucleoside triphosphate (NTP) for catalysis. The molecular mechanisms by which they control the rate and fidelity of NTP incorporation remain elusive. Here, we demonstrated through enzymology, virology and computational approaches that the R239 and K235 in the PB1 subunit of RdRp are critical to controlling the activity and fidelity of transcription. Contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
(90 reference statements)
1
5
0
Order By: Relevance
“…The oxygen atoms of P β interacted during the whole simulation with the positively charged Lys551 and Arg553 residues of motif F for both examined ternary complexes, thus contributing to the binding of CTP and ddhCTP. Our finding is in good agreement with the observations on other viral nucleic acid polymerases. ,,,, …”
Section: Results and Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The oxygen atoms of P β interacted during the whole simulation with the positively charged Lys551 and Arg553 residues of motif F for both examined ternary complexes, thus contributing to the binding of CTP and ddhCTP. Our finding is in good agreement with the observations on other viral nucleic acid polymerases. ,,,, …”
Section: Results and Discussionsupporting
confidence: 92%
“…It was suggested that during the reaction, a shrinking of this distance may occur, leading O3′ to become closer to Pα and consequently facilitating the nucleophilic attack. The little longer distance in ddhCTP than that in CTP could affect the O3′–P α alignment for catalysis during the nucleophilic attack, in the reactive Michaelis–Menten complex. …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, k cat ranging from 0.000105 s –1 to 680 s –1 were measured for a number of viruses, corresponding to 22.5 and 13.3 kcal mol –1 , respectively. , These values are, therefore, in reasonable agreement to the calculated energy of TSs presented here, as well as with those calculated for similar polymerases and enzymes catalyzing similar reaction. ,,,,, The reaction is exoenergetic, as expected, due to the cleavage of a highly energetic bond, and the NMP unit has been fully transferred, as reflected by the Pα–Oα distance of 5.641 Å, in CMP, and 4.098 Å, in ddhCMP. Finally, in analogy to other polymerases, ,, in RdRp:RNA-CMP:PPi and RdRp:RNA-ddhCMP:PPi, the observed formation of pyrophosphate molecule is assisted by the stabilization of Mg B 2+ (see O Pγ –Mg B 2+ distance of 1.960 Å for CMP and 1.955 Å for ddhCMP in Figure ). The PPi is involved in hydrogen bond interaction with Lys621 residue, which resembles the well-known role observed in other systems by histidine residue, implicated in the proton transfer necessary for the completion of the chemical process .…”
Section: Resultsmentioning
confidence: 73%